IMPLEMENTASI TEKNOLOGI PENGOLAHAN SAMPAH PLASTIK, KARET, DAN STYROFOAM SEBAGAI ENERGI ALTERNATIF - Bambang Sugiarto; Heru Sigit Purwanto; Fauzan Irfandi (Dharma: Jurnal Pengabdian Masyarakat, 2021)
Household waste, especially plastic, styrofoam and used tires, is a problem for the community because it reduces the quality of the environment. In addition, another problem faced by the community is the increase in household expenditure from consuming fuel for cooking. The community service team tries to overcome both of these problems by implementing waste-to-fuel processing technology. Community service activities include training, mentoring, and providing facilities for processing waste into environmentally friendly fuel. The activity was carried out at the Surolaras Waste Bank, Yogyakarta City. The benefits that are felt are reduced waste, fuel products that can be used for household needs, reduced household expenses, and a well-preserved natural environment.